Pelatihan Inovasi Produk Untuk Meningkatkan Daya Tarik Wisata Di Kampung Batik Tulis Giriloyo Di Yogyakarta - Harsoyo, Titik Desi; Puspitasari, Kakanita Ari (LP3M Universitas Putra Bangsa, 2023)
This community service program is carried out in Kampung Batik Tulis Giriloyo, which is located in Bantul Regency, DIY Province. The purpose of this training is to assist partners in solving marketing problems. Prior to this training, the products offered at tourist site were hand-drawn batik cloth, apparel, scarves and pashmina. Product innovation training was chosen as a solution program to help partners solve marketing problems. This training program is expected to be useful for handmade batik craftsmen in Kampung Giriloyo to increase their knowledge and skills regarding product innovation, especially ecoprint techniques and making accessories from batik patchwork waste. This training is expected to provide additional skills for craftsmen regarding product innovation by utilizing materials available around them. The training was held from October to November 2022, at the paguyuban hall and was held in three stages: (1) socialization on product innovation, (2) training on making ecoprint, (3) training on making accessories from batik patchwork waste. The outputs resulting from this training are: (1) handmade batik craftsmen gain new knowledge about the importance of product innovation for business sustainability, (2) craftsmen gain additional skills in making ecoprints, (3) craftsmen gain additional skills in making various accessories made from handmade batik patchwork. The training is expected to be useful for craftsmen in Kampung Batik Tulis Giriloyo to increase the attractiveness of tourists visiting the location.